A new subspecies of Carabus (Tribax) biebersteini Ménétries, 1832 from north Caucasus (Coleoptera: Carabidae) - Obydov, Dmitry (Acta entomologica slovenica (Ljubljana), 2011)
A series of specimens of Carabus (Tribax) biebersteini Ménétries, 1832 was collected in the north Caucasus (Stavropol Region, 33 km to the north-west from Kislovodsk City, Pastbischnyi Mt. Ridge). This locality is far from the area where known subspecies of Carabus (Tribax) biebersteini occur and steppe regions in-between probably isolate this population from them. The collected specimens differ from other subspecies by the shape, structure and coloration of the pronotum and elytra, and represent a new subspecies, Carabus (Tribax) biebersteini vlasenkoi ssp. n., which is described in this paper and which, most probably, is restricted to Pastbischnyi Mt. Ridge. Diagnostic characters are given.
Keywords: Carabidae; Carabini; Carabus (Tribax) biebersteini; Coleoptera; entomologija; entomology; favna; new subgenus; North Caucasus; severni Kavkaz; Stavropol Region; Stavropolska regija